2019
DOI: 10.1136/rmdopen-2019-001053
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac conduction disturbances in patients with ankylosing spondylitis: results from a 5-year follow-up cohort study

Abstract: ObjectivesTo describe electrocardiographic (ECG) development in patients with ankylosing spondylitis (AS) and identify associations between baseline characteristics and cardiac conduction disturbances (CCD) at 5-year follow-up.MethodsIn a longitudinal cohort study, 172 patients (54% men, mean age (SD) of 50 (13) years at baseline) with AS underwent ECG, physical examination, questionnaires and laboratory testing at baseline and at 5-year follow-up. Descriptive statistics and univariate and age- and sex-adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Conduction disorders as bundle-branch blocks (BBB), atrioventricular blocks (AVB), and intraventricular blocks have been frequently observed in patients with SpA, especially among those with associated valvular involvement and may require a pacemaker [ 19 , 29 31 ]. In the present study, only two patients (2.2%) had RBBB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conduction disorders as bundle-branch blocks (BBB), atrioventricular blocks (AVB), and intraventricular blocks have been frequently observed in patients with SpA, especially among those with associated valvular involvement and may require a pacemaker [ 19 , 29 31 ]. In the present study, only two patients (2.2%) had RBBB.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the prevalence in former studies varied from 1.1% [ 32 , 33 ] to 33% [ 34 , 35 ]. It was previously reported that the rates of conduction disturbances varied according to the disease duration but occurred among all ages [ 23 , 28 , 29 , 32 ]. Moreover, it was mentioned that HLA-B27 was strongly associated with conduction disturbances even in the absence of SpA and higher disease activity [ 16 , 29 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriatic arthritis (PsA) is an inflammatory disease characterized by psoriasis, arthritis, enthesitis and dactylitis [1]. Obesity, diabetes, hypertension, hyperlipidemia and the metabolic syndrome (MetS) are overrepresented in both psoriasis and PsA [2][3][4] and the patients are at increased risk of cardiovascular morbidity [5][6][7][8][9]. Studies indicate that obesity may play a pathophysiologic role in psoriasis and PsA, since obesity is associated with an increased risk of developing these conditions [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that cardiac conduction anomalies in AS may be associated with male sex, higher disease activity in addition to CV disease risk factors [ 45 ]. Increased prevalence of bradycardia and longer QTc intervals in patients with AS has also been reported [ 46 ].…”
Section: Reviewmentioning
confidence: 99%